2017
DOI: 10.2460/ajvr.78.8.977
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lidocaine on inflammation in equine jejunum subjected to manipulation only and remote to intestinal segments subjected to ischemia

Abstract: OBJECTIVE To examine effects of continuous rate infusion of lidocaine on transmural neutrophil infiltration in equine intestine subjected to manipulation only and remote to ischemic intestine. ANIMALS 14 healthy horses. PROCEDURES Ventral midline celiotomy was performed (time 0). Mild ischemia was induced in segments of jejunum and large colon. A 1-m segment of jejunum was manipulated by massaging the jejunal wall 10 times. Horses received lidocaine (n = 7) or saline (0.9% NaCl) solution (7) throughout anesthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…However, none of these studies examined long‐term survival and they were not all adequately randomised, used insufficient numbers to provide statistical power, included other drugs, involved high rates of lidocaine treatment under anaesthesia for control horses , and included diseases that might not represent the typical causes of POR . The absence of a prokinetic effect in normal horses , questionable antiinflammatory benefits , and absence of a favourable cost‐benefit analysis raise some concerns about the use of lidocaine. A recent study demonstrated that lidocaine did not affect the prevalence of POR, total reflux volume, duration of reflux and post‐operative survival after small intestinal surgery .…”
Section: Role Of Post‐operative Pharmacological Managementmentioning
confidence: 99%
“…However, none of these studies examined long‐term survival and they were not all adequately randomised, used insufficient numbers to provide statistical power, included other drugs, involved high rates of lidocaine treatment under anaesthesia for control horses , and included diseases that might not represent the typical causes of POR . The absence of a prokinetic effect in normal horses , questionable antiinflammatory benefits , and absence of a favourable cost‐benefit analysis raise some concerns about the use of lidocaine. A recent study demonstrated that lidocaine did not affect the prevalence of POR, total reflux volume, duration of reflux and post‐operative survival after small intestinal surgery .…”
Section: Role Of Post‐operative Pharmacological Managementmentioning
confidence: 99%
“…The effect of lidocaine on intestinal neutrophilic inflammation in horses has not been consistent in previous studies. One author reported reduced mucosal neutrophil counts when treatment with flunixin‐meglumine was combined with lidocaine administration,9 while another found no consistent decrease in neutrophil tissue infiltration 11. The exact mode of action of lidocaine on inflammatory cells has not been clarified; however, a recent study using murine neutrophils discovered that lidocaine influences the pivotal function of neutrophil sodium channels, thereby inhibiting their adhesion and migration 20.…”
Section: Discussionmentioning
confidence: 99%
“…In experimental models, it has been shown to have a beneficial effect on the intestine after ischaemia and reperfusion, by decreasing intestinal oedema,8 decreasing COX‐2 expression in intestinal mucosa9 and by limiting the increased gut wall permeability compared to flunixin‐meglumine administration alone 10. In a more recent experimental study, the horses treated with lidocaine did not show a consistent decrease in intestinal neutrophil infiltration compared to the untreated horses 11. Currently, the exact mechanism of these actions remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…), whereas a more recent study could not consistently demonstrate an antiinflammatory effect of lidocaine across all layers in different models of jejunal inflammation (Bauck et al . ). I fully agree and have stated that lidocaine does provide visceral analgesia (Freeman ), especially with flunixin meglumine (Cook et al .…”
mentioning
confidence: 97%
“…Undoubtedly surgically relevant manipulation does induce inflammation in intestinal muscle layers in horses (Bauck et al . ), but transferring this information from laboratory animals to POR in horses lacks support (Freeman ). For example, the inflammation theory for POR embraced by Dr Blikslager would seem to predict that a repeat celiotomy, with as much manipulation and inflammation as induced at the first surgery, would exacerbate POR; the opposite seems to be true (Bauck et al .…”
mentioning
confidence: 99%